2019
DOI: 10.1080/14397595.2019.1602292
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical immunoglobulins reduce neutrophil extracellular trap formation and ameliorate the development of MPO-ANCA-associated vasculitis

Abstract: Objectives Intravenous immunoglobulin (IVIG) therapy is effective against some autoimmune diseases. Although its efficacy on peripheral neuropathy due to eosinophilic granulomatosis with polyangiitis-one of myeloperoxidase-antineutrophil cytoplasmic antibody (MPO-ANCA)-associated vasculitis (MPO-AAV)-has been established, that on other MPO-AAV remains undetermined. We examined the effects of pharmaceutical immunoglobulins on the formation of neutrophil extracellular traps (NETs) related to MPO-ANCA production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 31 publications
(26 reference statements)
0
29
0
Order By: Relevance
“…IVIg may also influence the number and function of Tregs which help to control inflammation and inhibit T-cell activation [244], TNF-α production, and IL-6 and matrix metalloproteinase 9 activity. IVIg also reduces NET formation [245] and may have a role in modulating a regulatory autophagy. Moreover, Fc fragment and IVIg may reduce cytokine and DAMP production [246,247] and protect against HMGB1-induced cell death, modulating TLR and RAGE expression [248].…”
Section: Convalescent Plasma and Intravenous Immunoglobulinsmentioning
confidence: 99%
“…IVIg may also influence the number and function of Tregs which help to control inflammation and inhibit T-cell activation [244], TNF-α production, and IL-6 and matrix metalloproteinase 9 activity. IVIg also reduces NET formation [245] and may have a role in modulating a regulatory autophagy. Moreover, Fc fragment and IVIg may reduce cytokine and DAMP production [246,247] and protect against HMGB1-induced cell death, modulating TLR and RAGE expression [248].…”
Section: Convalescent Plasma and Intravenous Immunoglobulinsmentioning
confidence: 99%
“…Intriguingly, the amount of PMA-induced NETs was significantly lower when neutrophils were pre-treated with IVIG before exposure to PMA [121]. Moreover, the inhibitory effect of IVIG on NETs, as well as decreased ANCA titers and pulmonary haemorrhage, also was seen in peritoneal tissue of MPO-AAV rats treated with IVIG [121]. To conclude, the presence of NETs and their autoantigenic properties in AAV patients is well-demonstrated.…”
Section: Anti-neutrophil Cytoplasmic Antibodies (Anca) Vasculitis (Aav)mentioning
confidence: 78%
“…NET-induced endothelial cell damage can be prevented when NETs are degraded with DNase1 [55]. Intravenous immunoglobulin (IVIG) is a potential treatment for AAV patients [121]. Intriguingly, the amount of PMA-induced NETs was significantly lower when neutrophils were pre-treated with IVIG before exposure to PMA [121].…”
Section: Anti-neutrophil Cytoplasmic Antibodies (Anca) Vasculitis (Aav)mentioning
confidence: 99%
See 1 more Smart Citation
“…Antonelou et al showed that treatment with an MPO inhibitor reduced the production of NETs, ROS, and endothelial cell damage in mice and renal biopsies [ 175 ]. Intravenous immunogloblins, previously used to treat other autoimmune vasculitides, reduced the rate of pulmonary hemorrhage and peritoneal NETs in rat models of NETosis [ 176 ].…”
Section: Therapeutic Implications Of Biomarker Discoveriesmentioning
confidence: 99%